Division in Gender Roles During the Pandemic Crisis and Smart (Agile) Working - Martini, Elvira; Mebane, Minou Ella; Greco, Luca (Italian Sociological Review, 2023)
Gender inequality in domestic work still remains a major global issue, and it is particularly strong in Italy. Recent research (Istat, 2019) showed that Italy is the country with the greatest gender gap differences in Europe concerning time devoted to unpaid work. Agile work has recently received gotten considerable a lot of attention as being a possible solution to work-family conflict. During the COVID-19 crisis, Italy had one of the highest rises in the number of people partaking in agile work (Eurofound, 2020). Before the pandemic, only 10% of Italian people worked from home at least several times a week (compared to 15.8% on average in the EU-27), whereas 39.9% started working from home during the first wave of the pandemic (compared to 36.5% on average in the EU-27). This increase in agile working was higher for women (4.1% more than men) (RFL, 2020). Can forced agile working help to rebalance the roles of men and women in the Italian family? To try to answer this question, through this study, we aimed to ascertain if the massive gender disparity that characterizes Italy persisted during the lockdown when couples were compelled to stay home.